In Vitro and In Vivo Feedstuff Digestibility for Snook, Centropomus undecimalis, Juveniles. Issue 1 (25th May 2017) - Lemus, Iratzio; Maldonado, Carlos; Cuzon, Gerard; Sanchez, Adolfo; Gaxiola, Gabriela; Alvarez, Alfonso; Guerrero, Martha
Abstract: The degree of hydrolysis (DH) of the ingredients was evaluated for Centropomus undecimalis juveniles. The in vitro experiment included wheat gluten (WG), corn gluten (CG), soybean meal (SBM) and pretreated phytase (SBM + phytase), soy protein concentrate (SPC), canola meal (CAN) and pretreated phytase (CAN + phytase), poultry byproduct meal (PBPM), chicken meal (CHKM), dried whey (DW), Pota meal (PM: mix of giant squid, fish soluble protein concentrate, crustacean meal, and fish oil), and Protiblend (PTB: aquatic and render mix). The highest acidic DH occurred with PTB (0.38 ± 0.06), CHKM (0.33 ± 0.3), and PBPM (0.25 ± 0.03). In the alkaline condition, PTB (1.6 ± 0.17 and 0.98 ± 0.05 for pyloric caeca and intestine, respectively) and CG (1.04 ± 0.4 and 0.75 ± 0.2 for caeca and intestine, respectively) provided the highest DH values. In vitro digestibility demonstrated that PTB was the highest (85.3%) followed by PBPM (51.4%), CAN + phytase (47.6%), CG (45.1%), and CHKM (46.5%). The in vivo experiment concerned the WG, CHKM, PBPM, PM, and PTB diets plus a reference diet with fishmeal (Ref diet). The total %DH was different ( P < 0.05) with the lowest values for the WG diet (0.34 ± 0.09%) and Ref diet (0.34 ± 0.15). Free amino acid released during digestion was displayed for these diets and a bifactorial analysis produced no difference ( P > 0.05). The apparent digestive coefficients ranged from 89.8 to 92.9% for protein and from 68 to 71.4% for energy.